Hermeneutika Jasser Audah : Upaya Menyelesaikan Problem Sosial Kontemporer dengan Teori System dan Maqasyid al-Syariah - Abd Halim (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
This articel discusses the theory of system and maqashid syari’ah which has been initiated improved by Jasser Audah in overcoming contemporary social problem. Accoding to Jasser, maqasyid syariah which emphezises porposefulness needs six fitures of way of thought those are cognition, holistic, openness, multidimensionality, interrelatedness and purposefulness. By those fitures, one can understand syariah proportionally and appropriately in solving recently problem.